Correlation study of biomechanical changes between diabetic eye disease and glaucoma using finite element model of human eye with different iris-lens channel distances. (November 2022) - Yan, Yuwei; Shi, Huanhuan; Zhao, Yali; Cao, Yu; Xie, Zhihao
Highlights: Finite element models of human eyes with various iris-lens channel distances were constructed. Eye models were used to simulate the effect of pupillary block and abnormal aqueous flow induced by diabetes. Relationship of diabetes and glaucoma was investigated using unidirectional fluid-solid coupling numerical simulation. Abstract: Purpose: To find out the effect on the biomechanical response of the eye in the setting of diabetes combined with glaucoma. Method: Five finite element models of the human eyes with various iris-lens channel (ILC) distances (2 μm–20 μm) were constructed, respectively. The human eye model used for finite element analysis contain all the ocular contents and the optic nerve head. All these models with different ILC distances were used to simulate the effect of pupillary block and abnormal aqueous flow induced by diabetes. And those models were also used for the biomechanical properties study of ocular tissues under the elevated intraocular pressure (IOP), using unidirectional fluid-solid coupling numerical simulation method. Results: For the most severe cases of pupil block (2 μm), a significant difference in chamber pressure caused the iris to move forward and had posterior adhesion to the lens. And the strain, stress, and displacement of the whole eyeball were significantly higher than those of the other four cases, while the Optic Nerve Head (ONH) region was the opposite. The promotion of IOP to biomechanical response at both global eye and ONH region was close to the normal eye conditions, or even ease for ILC = 2 μm. But in the cases of glaucoma with pupil block and high aqueous flow, the biomechanical properties of the whole eyeball were remarkably enhanced for all IOP conditions. Less influence was observed in the ONH region. Conclusion: The promotion of diabetes for glaucoma is not directly on the optic nerve, instead, it indirectly affects the optic nerve by affecting the global eye. Glaucoma combined with diabetes complications may increase the biomechanical damage of IOP to the whole eye.